Behavioral pathway to a broken heart: The link between adverse childhood experiences, depression, physical exercise and cardiovascular health - Bertele, Sebastian; Heitland, Ivo; Fraccarollo, Daniela; Stapel, Britta; Bauersachs, Johann; Westhoff-Bleck, Mechthild; Kahl, Kai G. (Frontiers in Psychiatry, 2022)
Background and aim Adverse childhood experiences (ACEs) are a major risk factor for unfavorable behavioral, mental and health outcomes later in life. However, the precise pathway via which ACEs convey these risks, in particular regarding health outcomes such as cardiovascular disease, remains unknown. Here, we combined psychiatric and cardiac methods to investigate the pathway via which childhood adversities may lead to adult adverse cardiovascular health, with a focus on epicardial adipose tissue (EAT) as a risk marker. Methods 210 adult congenital heart disease outpatients (mean age 35.5 y, 43% female) completed a thorough cardiac and psychiatric evaluation. Psychiatric measurements included an expert interview, the childhood trauma questionnaire (CTQ), Beck's depression inventory II (BDI-II), quality of life and the global scale of functioning, amongst others. All patients completed a full cardiac workup including EAT assessment using echocardiography. We then computed bootstrapping mediation models using ACEs as a predictor, depression and physical activity as mediators and EAT as dependent variable in PROCESS. Results CTQ scores had a significant indirect effect on EAT via a serial mediation of BDI and physical activity [a*b2*d = 0.0260, 95% BCa CI [0.0047, 0.0619]]. Conclusion Using mediation analyses, we show that adverse childhood events are linked to increased depressive symptoms, which are linked to decreased physical activity, which in turn are linked to a higher amount of epicardial adipose tissue. While other pathways most certainly exist and replication is needed, this suggests a meaningful pathway via which ACEs lead to adverse cardiovascular health, with several potential targets for health interventions across time.